Preservation of Kidneys by Machine Perfusion Influences Gene Expression and May Limit Ischemia/Reperfusion Injury. (March 2014) - Wszola, Michal; Kwiatkowski, Artur; Domagala, Piotr; Wirkowska, Agnieszka; Bieniasz, Monika; Diuwe, Piotr; Kieszek, Rafał; Durlik, Magdalena; Chmura, Andrzej
Context: Machine perfusion improves graft survival. Histopathologic analysis reveals a lower incidence of chronic rejection and interstitial fibrosis in kidneys preserved with machine perfusion. Ischemic/reperfusion injury may help to explain these findings. Objective: To assess the activation of genes correlated with ischemic/reperfusion injury in kidneys preserved under different conditions before transplant. Design/Patients: Between 2005 and 2006, 69 kidney biopsy specimens were collected and patients were followed up for 5 years after that. Intervention: Before transplant, kidneys were preserved with machine perfusion or cold storage. Donors from the machine perfusion and cold storage groups did not differ with regard to age, sex, or hemodynamic status. Recipients were divided into 5 groups: expanded criteria donor–machine perfusion (n = 16), standard criteria donor–machine perfusion (n = 10), expanded criteria donor–cold storage (n = 9), and standard criteria donor–cold storage (n = 27); 7 kidneys were retrieved from living related donors. Main Outcome Measures: Biopsies were done 30 minutes after reperfusion. Interleukin-1β, vascular endothelial growth factor, heme oxygenase-1, and hypoxia-inducible factor–1 gene expression levels were analyzed. Results: Mean expression levels of hypoxia-inducible factor–1α were significantly higher in the cold storage groups, and lower in the machine perfusion and living-related donor groups. Five-year graft survival was significantly ( P < .05) lower in the expanded criteria donor–cold storage group (66%) than in the standard criteria donor–machine perfusion group (90%). Machine perfusion influences gene expression related to hypoxia during reperfusion and may improve the long-term results of kidney transplant.